When and Why Do Takeovers Lead to Fraud?. Issue 1 (25th April 2018) - Byun, Hee Sub; Kim, Woojin; Lee, Eun Jung; Park, Kyung Suh
Abstract: This paper develops a model explaining how acquisitions of controlling block ownership can facilitate post‐takeover fraud by new managers when investor protection is poor. Based on disclosures of embezzlement or breach of fiduciary duty in Korean firms, we find that the probability of explicit looting in takeover targets is 13%, almost five times as large as a matched sample of non‐targets. Post‐takeover frauds are primarily driven by transfers of minority blocks, while the corresponding probability in majority acquisitions is statistically indistinguishable from the non‐targets. These findings may explain why minority acquisitions of controlling blocks are popular under poor investor protection.